EVALUASI KECERNAAN RUMPUT KUMPAI MINYAK (Hymenachne amplexicaulis) AMONIASI SECARA IN VITRO - Akhadiarto, Sindu; fariani, a (Jurnal Sains dan Teknologi Indonesia, 2012)
The objective of this research was to study digestibility of kumpai minyak (Hymenachne amplexicaulis) amoniation by in vitro techniques. Materials used in this study were : kumpai oil grass; poultry manure; urea; cattle rumen fluid; Mc buffer solution Dougall; NaOH or H3PO4 and saturated HgCl2. This research was held in two stage, the first was amoniation of kumpai minyak and second was in vitro analysis, both experiment was held at laboratory of Nutrition and Feed Animal, Agriculture Faculty at Sriwijaya University. The research used completely randomized design with 4 treatments and 4 replications which were: A0 (kumpai oil grass without urea), A1 (kumpai oil grass with urea 2%), A2 (kumpai oil grass with urea 4%) and A3 (kumpai oil grass with urea 6%). Parameters measuredwere dry matter digestibility, organic matter digestibility and gas production.. The result showed that the treatment were significantly difference (P<0.01) on organic matter digestibility, but non sinificantly differences (P>0.01) on dry matter digestibility and gas production.